2020
DOI: 10.1002/ijc.33046
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibition prevents the growth of primary and metastatic osteosarcoma

Abstract: Overall survival rates for patients with advanced osteosarcoma have remained static for over three decades. An in vitro analysis of osteosarcoma cell lines for sensitivity to an array of approved cancer therapies revealed that panobinostat, a broad spectrum histone deacetalyase (HDAC) inhibitor, is highly effective at triggering osteosarcoma cell death. Using in vivo models of orthotopic and metastatic osteosarcoma, here we report that panobinostat impairs the growth of primary osteosarcoma in bone and spontan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…OS metastasis and chemoresistance are the key clinical factors leading to a low five-year survival rate of approximately 30% in patients with remote involvement [3][4][5][6]. Recent studies have shown that tumor suppressor and/or oncogene mutations, copy number alterations, fusion genes, and epigenetic dysregulation may lead to tumor formation, cancer metastasis, and multidrug resistance [7][8][9][10][11]. These distinct characteristics may pose as vulnerabilities that can be exploited as treatment targets.…”
Section: Introductionmentioning
confidence: 99%
“…OS metastasis and chemoresistance are the key clinical factors leading to a low five-year survival rate of approximately 30% in patients with remote involvement [3][4][5][6]. Recent studies have shown that tumor suppressor and/or oncogene mutations, copy number alterations, fusion genes, and epigenetic dysregulation may lead to tumor formation, cancer metastasis, and multidrug resistance [7][8][9][10][11]. These distinct characteristics may pose as vulnerabilities that can be exploited as treatment targets.…”
Section: Introductionmentioning
confidence: 99%
“…Romidepsin, which is a histone deacetylase (HDAC) inhibitor, is approved for the treatment of hematologic malignancies and shows limited activity in a number of solid tumor types with notable toxicities [50][51][52][53][54] . Several groups have reported that HDAC inhibitors prevent the growth of OS cell lines in vitro and in vivo 55,56) . Although the effects of romidepsin on ESOS have never been reported, our data support the hypothesis that romidepsin may represent a potential strategy for OS and ESOS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HDAC1 was significantly downregulated in our transcriptome analysis. Treatment with panobinostat, a broad spectrum HDAC inhibitor, showed decreased OS growth and lung metastasis in an orthotopic xenograft model using human OS cell lines (29). In this report, treatment with the selective inhibitor for HDAC1/2 compromised the growth of OS in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%